AnalysisAnalysis of Gold Price Fluctuations in Indonesia in the Third Quarter of 2025 of Gold Price Fluctuations in Indonesia in the Third Quarter of 2025 - Diana Magfiroh; Komarudin Komarudin (Return : Study of Management, Economic and Bussines, 2025)
This study examines the fluctuations of domestic gold prices in Indonesia during the third quarter of 2025, which were influenced by complex interactions between global and domestic macroeconomic factors. Gold plays a crucial role as an investment instrument and hedge asset, making it important to understand the determinants of its price movements, particularly in emerging markets such as Indonesia. This research aims to analyze the influence of external factors, including world gold prices, rupiah exchange rates, global inflation, and global interest rates, on domestic gold price fluctuations. This study employs a quantitative approach using time series data for the period July–September 2025. The analysis methods include multiple linear regression (OLS) to examine the simultaneous effects of variables, the GARCH model to analyze volatility patterns, and the Granger causality test to identify causal relationships among variables. The results indicate that world gold prices and rupiah exchange rates have a significant and dominant influence on domestic gold prices, while global interest rates also show a meaningful effect. In contrast, global inflation does not have a significant direct impact. Furthermore, gold price volatility exhibits a clustering pattern, indicating that periods of high volatility tend to be followed by similar conditions. In conclusion, domestic gold price movements in Indonesia are strongly driven by external macroeconomic factors, particularly global gold prices and exchange rate dynamics. This study contributes to the literature by integrating regression, volatility, and causality analysis within a specific quarterly context. The findings imply that investors and policymakers should closely monitor global economic indicators to manage risks and formulate effective strategies in responding to gold market fluctuations